Biodiesel production by lipase-catalyzed transesterification of Ocimum basilicum L. (sweet basil) seed oil. (15th January 2017) - Amini, Zeynab; Ong, Hwai Chyuan; Harrison, Mark D.; Kusumo, Fitranto; Mazaheri, Hoora; Ilham, Zul
Highlights: Need for alternative energy has led to explore new feedstock. Ocimum basilicum seeds oil was used as biodiesel feedstock. Biodiesel was produced via lipase-catalyzed transesterification by Novozym. Artificial neural network with genetic algorithm modelling was employed. Abstract: The increasing global demand for fuel, limited fossil fuel resources, and increasing concern about the upturn in gaseous CO2 emissions are the key drivers of research and development into sources of renewable liquid transport fuels, such as biodiesel. In the present work, we demonstrate biodiesel production from Ocimum basilicum (sweet basil) seed oil by lipase-catalyzed transesterification. Sweet basil seeds contain 22% oil on a dry weight basis. Artificial neural network with genetic algorithm modelling was used to optimize reaction. Temperature, catalyst concentration, time, and methanol to oil molar ratio were the input factors in the optimization study, while fatty acid methyl ester (FAME) yield was the key model output. FAME composition was determined by gas chromatography mass spectrometry. The optimized transesterification process resulted in a 94.58% FAME yield after reaction at 47 °C for 68 h in the presence of 6% w/w catalyst and a methanol to oil ratio of 10:1. The viscosity, density, calorific value, pour point, and cloud point of the biodiesel derived from sweet basil seed oil conformed to the EN 14214 and ASTM D6751 standard specifications. The antioxidant stability of the biodiesel did not meet these specifications but could be improved via the addition of antioxidant.